Pengolahan Data Keuangan Pada CV Ciremai Cipta Mandiri (Binatuku Laundry Advisor) Menggunakan Zahir Accounting Versi 6.0 - Nurleni, Nurleni; Swastika, Rahayu; Daniel, Daniel (LPPM Universitas Bina Sarana Informatika, 2023)
CV Ciremai Cipta Mandiri (Binatuku Laundry Advisor) is a company engaged in trade and services. The system for calculating financial reports is still carried out using the Microsoft Excel application starting from collecting transactions, recording transactions by entering cash in and cash out to other financial reports, this can cause errors when recording transactions in progress, inaccurate financial reports and delays in finding data required. Manual processing can cause weaknesses in Accounting data processing and cause errors in the recording process and the accuracy of reports that occur can result in errors in future financial statements. In this case CV Ciremai Cipta Mandiri (Binatuku Laundry Advisor) requires an Accounting system or software to make it easier for owners and employees to process detailed and complete company financial data, so that company owners can find out the amount of income and expenses in each period. One of them is the use of Accounting-based computer applications or software in processing financial data using Zahir Accounting Version 6.0, which is the best solution to overcome the problems that exist in this company. A computerized system is better than a system that still uses regular records, therefore with the Zahir Accounting software it is hoped that an effective and efficient activity can be achieved that can support the activities of this company.